Inspeksi Sanitasi Masjid dan Perilaku Marbot di Wilayah Kerja Puskesmas Kijang Kabupaten Bintan Tahun 2025 - Putri, Nurfadilahni’mah; Pitriyanti, Luh; Samosir, Kholilah (Jurnal Sanitasi Profesional Indonesia, 2025)
Mosque sanitation is an effort to control and monitor facilities such as clean water, toilets, waste management systems, and trash bins, which are related to the risk of disease transmission. Poor sanitation can trigger the emergence of diseases; therefore, routine maintenance, facility repairs, and adequate hygiene facilities are necessary. In the working area of Kijang Public Health Center, mosque sanitation issues are still found, such as uncovered trash bins, dirty and foul-smelling toilets, and the absence of tissues and soap. Inadequate ventilation and humidity also pose health risks to congregants. Mosque caretakers (marbot) play an important role in maintaining cleanliness and comfort within the mosque. This study aims to determine the condition of mosque sanitation and marbot behavior in the working area of Kijang Public Health Center. A descriptive survey design was used, through observation and interviews guided by Ministry of Health Regulation No. 2 of 2023. The total sample consisted of 18 mosques and 18 marbots selected using total sampling technique, with data collection conducted in March–April 2025 and analyzed univariately. The results showed that all mosque environments (100%) met the required standards, 16 mosque buildings (88.9%) met the standards, and only 10 mosques (55.6%) had sanitation facilities that met the standards. In terms of marbot behavior, 14 marbots (77.8%) had moderate knowledge, 9 marbots (50%) showed good attitudes, and all marbots (100%) demonstrated good practices. Continuous improvement of sanitation facilities and regular marbot training are necessary to create healthy and proper mosque environments.